Study on the Form of Electricity Theft in Area X - Hardianto Hardianto; Akbar Akbar (International Journal of Multi Discipline Science, 2021)
The behavior of theft of electricity is a form of violation that harms many parties. This research aims to know the violation class and category of violations by electricity customers in 3 years. The research approach used was qualitative research. The data sources in this study involved 1 management party, customers in the 1st year were 1,200 people, the 2nd year were 1,200 people, and the 3rd year were 700 people. Data collection techniques used were observation, documentation, literature study, and interviews. All data were analyzed inductively including data reduction, data presentation, and verification (arranging conclusion). The results of the research showed that the total number of violations for 3 years reached 7.1% which was distributed to 2.2% for class violations and 4.9% for categories of violations. The category of violations that occurred on the customer's side showed that it was greater than class violations. The number of class 3 violations reached 0.9% and violations of this class were higher than other classes. Meanwhile, the kWh violation category reached 2.6% and this violation category was higher than other categories. Based on the rate of the number of violations each year, there was an increase in violations by 0.2% – 0.9%.